Edukasi Pengetahuan Bijak Mengelola Pinjaman Bagi Ibu-Ibu Gereja Mission Batak - Desma Erica Maryati Manik; Hommy Dorthy Ellyany Sinaga; Elisabeth Nainggolan (LPPM STIM Sukma, 2023)
Knowledge of financial management is very important in supporting economic functions, especially improving community welfare, especially in families. Education on wise knowledge of managing loans for Mission Batak Church mothers is a Community Service Activity that aims to provide benefits for families in planning, managing financial resources more optimally and effectively, especially those derived from loans so as to improve family welfare. In addition, through education on wise knowledge of managing financial loans can provide information on access to financial institutions that are expected to make decisions on effective investment and financial planning to improve people's lives. Education on loan management is correlated with poverty so that increased knowledge of loan management is expected to make better financial decisions so that family or personal financial planning becomes more optimal and family welfare can be achieved.